2018
DOI: 10.1111/acem.13431
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Pediatric NEXUS II Head Computed Tomography Decision Instrument for Selective Imaging of Pediatric Patients with Blunt Head Trauma

Abstract: The Pediatric NEXUS Head CT DI reliably identifies blunt trauma patients who require head CT imaging and could significantly reduce the use of CT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…It is not clear if a multicentre prospective study of NEXUS II from Korea includes any children 19. Recently, the original team which derived the NEXUS II CDR conducted a validation study in a new data set including 11 750 blunt head injuries20; in an analysis of the paediatric cohort of 1018 children sensitivity was 98.0% (95% CI 89.1% to 99.9%) and specificity of 34.0% (95% CI 31.0% to 37.0%) for the assessment of high-risk status in patients with ICI 21. However, similar to the derivation cohort only patient who had received a CT scan were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear if a multicentre prospective study of NEXUS II from Korea includes any children 19. Recently, the original team which derived the NEXUS II CDR conducted a validation study in a new data set including 11 750 blunt head injuries20; in an analysis of the paediatric cohort of 1018 children sensitivity was 98.0% (95% CI 89.1% to 99.9%) and specificity of 34.0% (95% CI 31.0% to 37.0%) for the assessment of high-risk status in patients with ICI 21. However, similar to the derivation cohort only patient who had received a CT scan were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, a major disadvantage is the exposure of patients to ionizing radiation. 1,7 On the other hand, MRI demonstrates to be less accessible, have higher costs and be less tolerable among younger children when compared to CT. 2,7 However, It is a The NEXUS instrument, for head CT, enabled the identification of pediatric patients with blunt trauma that really needed a CT, which can significantly reduce the use of this imaging examination in children.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis conducted in the USA 1 showed that CT is related to future risks of developing malignanies, 1,11 especially in younger patients, 1 for being an examination that uses ionizing radiation.…”
Section: Nd Category -The Relation Between Ionization and Possible Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The CATCH rule (Canadian Assessment of Tomography for Childhood Head injury) [51] was evaluated in 11 studies [48, 5861, 63, 66, 72, 8183]. The NEXUS II rule (National Emergency X-Radiography Utilization Study) [50, 54] was evaluated in four studies [48, 8486]. Palchak rule [52] was evaluated in two studies [48, 87].…”
Section: Resultsmentioning
confidence: 99%